2016
DOI: 10.1111/jofi.12369
|View full text |Cite
|
Sign up to set email alerts
|

Short Selling and Earnings Management: A Controlled Experiment

Abstract: During 2005 to 2007, the SEC ordered a pilot program in which one-third of the Russell 3000 index were arbitrarily chosen as pilot stocks and exempted from shortsale price tests. Pilot firms' discretionary accruals and likelihood of marginally beating earnings targets decrease during this period, and revert to pre-experiment levels when the program ends. After the program starts, pilot firms are more likely to be caught for fraud initiated before the program, and their stock returns better incorporate earnings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
199
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(227 citation statements)
references
References 88 publications
14
199
0
1
Order By: Relevance
“…Finally, our study provides additional evidence on the effect of short selling regulation. Recent research examines the effect of Reg SHO on short selling activities and market quality (Diether, Lee, and Werner [2009]), corporate financing and investment decisions (Grullon, Michenaud, and Weston [2012]), the design of CEO compensation contracts (Angelis, Grullon, and Michenaud [2013]), and earnings management (Fang, Huang, and Karpoff [2013]). Our study contributes to this line of research by examining the effect of Reg SHO on corporate voluntary disclosure decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our study provides additional evidence on the effect of short selling regulation. Recent research examines the effect of Reg SHO on short selling activities and market quality (Diether, Lee, and Werner [2009]), corporate financing and investment decisions (Grullon, Michenaud, and Weston [2012]), the design of CEO compensation contracts (Angelis, Grullon, and Michenaud [2013]), and earnings management (Fang, Huang, and Karpoff [2013]). Our study contributes to this line of research by examining the effect of Reg SHO on corporate voluntary disclosure decisions.…”
Section: Introductionmentioning
confidence: 99%
“…According to a 2008 NYSE survey, managers appear to be aware of and sensitive to the impact of eliminating price tests on the amount of short-selling in their firms(Grullon, Michenaud, and Weston [2012],Fang, Huang, and Karpoff [2013]). They also should have known whether their firms were selected for the experiment given the public disclosure of the list of pilot securities on the SEC's Web site several months before implementation of Reg SHO and the extensive financial media coverage of the experiment.…”
mentioning
confidence: 99%
“…Karpoff et al (2010) [4], Hirshleifer et al (2011) [5] found that short selling can restrain the financial fraud. Chen et al (2015) [12], Fang et al (2016) [13] found that short selling can restrain earnings management and improve the reliability of financial information. Li (2017) [14] found that the introduction of short selling significantly improved the quality of the target company's information disclosure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following Fang et al (2016), we use a DiD approach in the following regression models (Eqns 1 and 2) to identify a causal relationship between short-selling constraints and corporate payouts.…”
Section: Regression Modelsmentioning
confidence: 99%
“…the 2004 Regulation SHO pilot program (see next paragraph)) to investigate whether relaxing short-sale constraints affects corporate decisions, such as investment and financing (Grullon et al, 2015), earnings management (Fang et al, 2016) and design of compensation contracts (De Angelis et al, 2017). A strand of studies examines the relationship between short selling and corporate decisions using conventional fixed-effects regression analysis.…”
Section: Introductionmentioning
confidence: 99%